Effect Of Secondary Metabolites Of The Seaweed (Halimeda Micronesia) At Lakshadweep Islands Against Aquatic Pathogens - R.GANESHAMURTHY; T.T.AJITH KUMAR; N.B.DHAYANITHI (International Journal of Pharma and Bio Sciences, 2012)
Marine ornamental fishes are remarkably valuable due to their high demand in domestic and international markets. It is a growing global interest to maintain these fishes in captivity. The bacterial and fungal infection is the major drawbacks in captive condition. In the present study, in-vitro screening of organic solvent extracts (methanol and acetone) of green algae Halimeda micronesia were tested against the aquatic pathogens Providencia rettgeri, Aeromonas hydrophila, Vibrio alginoticus, V. parahaemolyticus, Proteus proteus, Pseudomonas flurescens, Entrobacter sp, Flavobacterium sp, Edwarsiella tarda, and micrococcus sp. The antibacterial activity assay was tested using agar well diffusion method and the zone of inhibition was compared with the same produced by the antibiotic (Chloramphenicol) as a positive control. Crude extracts were analyzed with Fourier transform infrared spectroscopy (FT-IR) for identifying functional group of the crude extract.